Proper motion of the Magellanic Bridge: Removal of foreground stars. Issue Volume 14:Issue S353(2019) (June 2019) - Schmidt, Thomas; Cioni, Maria-Rosa L.; Niederhofer, Florian; Diaz, Jonathan; Queiroz, Anna B. A.; Matijevic, Gal; Chiappini, Cristina
Abstract: The Large and Small Magellanic Cloud (LMC and SMC) are the most luminous dwarf galaxy satellites of the Milky Way. Thanks to their close proximity (50-60 kpc), they provide one of the best opportunities to study in detail the kinematics of resolved stellar populations in an interacting pair of galaxies. Large photometric surveys like the ongoing Gaia mission and the near-infrared VISTA survey of the Magellanic Cloud system (VMC) will have a significant impact on our insight into the Magellanic system. We have combined the individual strengths of VMC and Gaia DR2 data to improve our understanding of the internal kinematics of the galaxies. In this study, we present results from our ongoing project dedicated to measure and analyse the proper motions of large samples of stars across the Magellanic Clouds, efficiently removing Milk Way foreground stars utilising distances derived with the StarHorse code.